Efficient Cocaine Degradation by Cocaine Esterase-Loaded Red Blood Cells - Rossi, Luigia; Pierigè, Francesca; Agostini, Marco; Bigini, Noemi; Termopoli, Veronica; Cai, Yingting; Zheng, Fang; Zhan, Chang-Guo; Landry, Donald W.; Magnani, Mauro (Frontiers in Physiology, 2020)
Recombinant bacterial cocaine esterase represents a potential protein therapeutic for cocaine dependence treatment. Unfortunately, the native enzyme was highly unstable and the corresponding mutagenized derivatives, RBP-8000 and E196-301, although improving in vitro thermo-stability and in vivo half-life, were a partial solution to the problem. For cocaine dependence treatment, an efficient cocaine-metabolizing enzyme with a longer residence time in circulation would be needed. We investigated in vitro the possibility of developing red blood cells (RBCs) loaded with RBP-8000 and E196-301 as a biocompatible system to metabolize cocaine for a longer period of time. RBP 8000 stability within human RBCs is limited (approx. 50% residual activity after 1 h at 37°C) and not different as for the free enzyme, while both free and encapsulated E196-301 showed a greater thermo-stability. By reducing cellular glutathione during the loading procedure, in order to preserve the disulphide bonds opportunely created to stabilize the enzyme dimer structure, it was possible to produce an encapsulated protein maintaining 100% stability at least after 4 h at 37°C. Moreover, E196-301-loaded RBCs were efficiently able to degrade cocaine in a time- and concentration-dependent manner. The same stability results were obtained when murine RBCs were used paving the way to preclinical investigations. Thus, our in vitro data show that E196-301-loaded RBCs can act as efficient bioreactors in degrading cocaine to non-toxic metabolites to be possibly considered in substance-use disorder treatments. This approach should now be investigated in a preclinical model of cocaine dependence to evaluate if further protein modifications are needed to further improve long term enzyme stability.